Techno-economic feasibility of lighting protection of overhead transmission line with multi-chamber insulator arrestors. (2018) - Hemapala, K.T.M.U.; Gnana Swathika, O.V.; Dharmadasa, K.P.R.D.S.K.
Abstract: The performance of transmission lines has a significant impact on reliability aspects of the power supply system of a country. The lightning back flashover effects are recognized as one of the major causes of transmission line outages. This paper focuses on studying the effect of Multi Chamber Insulator Arresters (MCIA) on lightning back flashover by transient modeling and subsequent simulation of a selected transmission line. Power System CAD (PSCAD) software program is utilized as the software tool for modeling and simulation of the 132 kV, Matugama-Kukule transmission line for this study. Simulation of the created transmission line model is carried out with and without MCIA to evaluate the improvements in lightning back flashover performance after installation of MCIAs in this transmission line. This analysis will contribute to improve the reliability of the Sri Lankan electrical power system.